Freestanding Film
By using a self-supporting film packaging cleaner containing crosslinked cellulose ether and polyethyl ether groups, the problem of inappropriate viscosity of traditional cleaner formulations is solved, and better cleaning performance and stability is achieved.
Patent Information
- Application Number
- JP2024544821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2023-02-10
- Publication Date
- 2025-03-21
AI Technical Summary
It is difficult for existing water-soluble packaging materials to mix traditional cleaner formulas stably, resulting in inappropriate viscosity of the cleaner and affecting cleaning performance.
A self-supporting film containing 20-100% crosslinked cellulose ether is used, which provides a stable crosslinking structure and appropriate viscosity adjustment effect at a polyether group content of 0.1-0.6%.
By using this self-supporting film packaging cleaner formulation, the viscosity of the cleaner can be significantly improved, the cleaning performance can be improved, and it can effectively resist corrosion of high concentration cleaner.
Smart Images

Figure 2025507515000001 
Figure 2025507515000002 
Figure 2025507515000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a self-supporting film, specifically, the self-supporting film comprising 20-100% by weight of a crosslinked cellulose ether, based on the weight of the self-supporting film, the crosslinked cellulose ether containing 0.1-0.6% by weight of a polyether group, based on the weight of the crosslinked cellulose ether, and unit dose detergent packages made with the self-supporting film.
[0002] Conventional water-soluble polymer films find use as packaging materials that facilitate the simplification of dispersion, injection, dissolution and dosing of materials to be delivered.For example, packages prepared from conventional water-soluble films are commonly used to contain pre-measured unit doses of household care compositions, such as hard surface cleansers, dishwashing detergents, and laundry detergent formulations.Since these household care compositions are generally effective in solution with water, it is possible to provide a concentrate that can be mixed with water to form a cleaning solution.The concentrate may be packaged and shipped separately from the bulk of the water used to make the cleaning solution.The end user can then form a cleaning solution from the water and the concentrate.
[0003] The problem with concentrates is that they must be mixed precisely to ensure the proper concentration of actives in the resulting household care composition to be effective. A solution that is too dilute may result in poor cleaning performance. A solution that is too concentrated may leave residue on the cleaned surface. Additionally, a cleaning solution that is too concentrated may result in wasted cleaning concentrate.
[0004] To alleviate concerns regarding improper dilution of the cleaning concentrate, it has been found to be beneficial to package a single pre-measured amount of the cleaning concentrate in an individual package. The pre-measured amount of the cleaning concentrate is preferably added to a specific amount of water to form an appropriately concentrated cleaning solution. Additionally, the concentrate can be packaged in a suitable sized container, and the user simply places the cleaning concentrate in the container and fills the remainder of the container with water. When the container is empty, a replacement package of the concentrate can be placed in the container and the remainder can be filled again with water.
[0005] It has also been found to be useful to package the cleaning concentrate in a water-soluble package, especially in a single pre-measured use amount. Formation of the cleaning solution is made easy with the water-soluble package containing the concentrate, as the user simply adds the water-soluble package to a container and adds the appropriate amount of water to form the desired cleaning solution. When the water-soluble package dissolves, the cleaning agent is released and a cleaning solution having the appropriate concentration of cleaning agent is formed.
[0006] One problem with concentrates that are conventionally packaged in water-soluble packages is that the cleaning formulations formed therewith have inadequate viscosity, given the difficulty of stably formulating conventional rheology modifiers into concentrated cleaners that are packaged.The lack of viscosity in cleaning compositions formed from packaged concentrates can be viewed negatively by consumers, for example in hand dishwashing formulations, and can adversely hinder performance in hard surface cleaners where rheology may be required, for example vertical adhesion for cleaning bathroom tiles.
[0007] Therefore, there remains a need for a unit dose detergent package for preparing a household care composition, where the household care composition formed has an improved viscosity. In particular, there remains a need for a free-standing film composition that can impart a thickening effect to the household care composition formed by the unit dose detergent package made with such a free-standing film composition.
[0008] The present invention provides a free-standing film comprising 20 to 100% by weight of a crosslinked cellulose ether, based on the weight of the free-standing film, the crosslinked cellulose ether containing 0.1 to 0.6% by weight of a polyether group, based on the weight of the crosslinked cellulose ether.
[0009] The present invention provides a free-standing film comprising 20 to 100% by weight of a crosslinked cellulose ether, based on the weight of the free-standing film, and a crosslinked cellulose ether containing 0.1 to 0.6% by weight of a polyether group, based on the weight of the crosslinked cellulose ether, wherein the crosslinked cellulose ether is an irreversibly crosslinked cellulose ether.
[0010] The present invention provides a free-standing film comprising 20 to 100% by weight of crosslinked cellulose ether, based on the weight of the free-standing film, and a crosslinked cellulose ether containing 0.1 to 0.6% by weight of a polyether group, based on the weight of the crosslinked cellulose ether, and having an average thickness of 5 to 200 μm.
[0011] The present invention relates to a self-supporting film, comprising 20-100% by weight, based on the weight of the self-supporting film, of a crosslinked cellulose ether, the crosslinked cellulose ether containing 0.1-0.6% by weight of a polyether group, based on the weight of the crosslinked cellulose ether; (a) 5-80% by weight, based on the weight of the self-supporting film, of a partially hydrolyzed poly(vinyl acetate); (b) 0.1-45% by weight, based on the weight of the self-supporting film, of a crosslinking agent; (c) 0.1-45% by weight, based on the weight of the self-supporting film, of a poly(ethylene oxide) having a weight average molecular weight of 20,000-2,000,000 Daltons; (d) a crosslinked cellulose ether having a weight average molecular weight of 20,000-2,000,000 Daltons; (e) at least one of the following: 0.1 to 35 weight percent, based on the weight of the free-standing film, of a poly(alkylene glycol) having a weight average molecular weight of greater than 400 to 5,300 Daltons; (f) 0.1 to 45 weight percent, based on the weight of the free-standing film, of a plasticizer; (g) 0.1 to 10 weight percent, based on the weight of the free-standing film, of a poly(isobutylene-co-maleic anhydride) copolymer, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized; and (g) 0.01 to 1.8 weight percent, based on the weight of the free-standing film, of poly(vinylpyrrolidone).
[0012] The invention provides a unit dose detergent package comprising the self-supporting film of the invention and a detergent formulation comprising 10-60% by weight of a surfactant based on the weight of the detergent formulation, wherein the self-supporting film forms a cavity, the detergent formulation is disposed within the cavity, the detergent formulation is in contact with the self-supporting film, and the self-supporting film encapsulates the detergent formulation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have discovered a unique free-standing film that promotes significant thickening of end-use detergent formulations formed using unit dose packages that contain the free-standing film.
[0014] Unless otherwise indicated, ratios, percentages, parts, etc. are by weight.
[0015] As used herein, unless otherwise indicated, the term "molecular weight" or Mw refers to weight average molecular weight measured in the conventional manner using gel permeation chromatography (GPC) and polyacrylic acid standards. The GPC technique is described in detail in Modem Size Exclusion Chromatography, WW Yau, JJ Kirkland, DDBly; Wiley-Interscience, 1979, and A Guide to Materials Characterization and Chemical Analysis, JP Sibilia; VCH, 1988, p.81-84. Molecular weights are reported herein in units of Daltons.
[0016] As used herein and in the appended claims, the term "DS" means the number of alkyl-substituted OH groups per anhydroglucose unit in a cellulose ether, as determined by the Zeisel method.
[0017] As used herein and in the appended claims, the term "DS(methyl)" or "DS(M)" refers to the number of methyl-substituted OH groups per anhydroglucose unit in a cellulose ether as determined by the Zeisel method.
[0018] As used herein and in the appended claims, the term "MS" means the number of moles of etherifying reagent bound as an ether per mole of anhydroglucose units as hydroxyalkyl substituents in a cellulose ether, as determined by the Zeisel method.
[0019] As used herein and in the appended claims, the term "MS(hydroxyethyl)" or "MS(HE)" refers to the number of moles of etherifying reagent bound as an ether per mole of anhydroglucose unit as a hydroxyethyl substituent in a cellulose ether, as determined by the Zeisel method.
[0020] As used herein and in the appended claims, the term "MS(hydroxypropyl)" or "MS(HP)" refers to the number of moles of etherifying reagent bound as an ether per mole of anhydroglucose unit as a hydroxypropyl substituent in a cellulose ether, as determined by the Zeisel method.
[0021] The term "Zeisel method" refers to the Zeisel cleavage procedure for determining MS and DS. See G. Bartelmus and R. Ketterer, Zeitschrift für Analytische Chemie, Vol. 286 (1977, Springer, Berlin, DE), pages 161-190.
[0022] Preferably, the free-standing film of the present invention comprises 20 to 100% by weight (preferably at least 25% by weight, more preferably at least 40% by weight, and most preferably at least 60% by weight) (preferably 98% by weight or less, more preferably 95% by weight or less, and most preferably 90% by weight) of crosslinked cellulose ether based on the weight of the free-standing film, and contains 0.1 to 0.6% by weight of a polyether group based on the weight of the crosslinked cellulose ether (preferably, the crosslinked cellulose ether is an irreversibly crosslinked cellulose ether).
[0023] Preferably, the self-supporting film of the present invention has an average thickness of 5 to 200 μm (preferably 20 to 100 μm, more preferably 35 to 100 μm, and most preferably 40 to 85 μm).
[0024] Preferably, the free-standing films of the present invention have a disintegration time of less than 90 seconds when measured at 40° C. using distilled water according to MSTM 205.
[0025] Preferably, the free-standing films of the present invention are water-soluble. The term "water-soluble," as used herein with respect to the free-standing films of the present invention, means that when a sample of the free-standing film (0.5" x 1.5" x 76 μm) is placed in 20 mL of tap water having a temperature of 5-25° C. in a sample vial, allowed to stand for 2 minutes, then shaken for 60 seconds, and then filtered through a 0.025 mm mesh screen, only slight haze is observed and no residue or grit is observed, following the procedures described herein in the Examples.
[0026] Preferably, the free-standing films of the present invention are water soluble based on a film solubility test performed according to MSTM (MonoSol Standard Test Method) 205 in distilled water at 25°C.
[0027] Preferably, the free-standing film of the present invention comprises 20 to 100% by weight (preferably at least 25% by weight, more preferably at least 40% by weight, and most preferably at least 60% by weight) (preferably 98% by weight or less, more preferably 95% by weight or less, and most preferably 90% by weight or less) of a crosslinked cellulose ether based on the weight of the free-standing film, and the crosslinked cellulose ether contains 0.1 to 0.6% by weight of a polyether group based on the weight of the crosslinked cellulose ether, the crosslinked cellulose ether comprises a base cellulose ether and a crosslinking bond, the crosslinking bond contains a polyether group, and the base cellulose ether is a mixed cellulose ether containing a hydroxyalkyl ether group and an alkyl ether group. More preferably, the free-standing film of the present invention comprises 20 to 100 wt % (preferably at least 25 wt %, more preferably at least 40 wt %, and most preferably at least 60 wt %) (preferably 98 wt % or less, more preferably 95 wt % or less, and most preferably 90 wt % or less) of a crosslinked cellulose ether based on the weight of the free-standing film, the crosslinked cellulose ether containing 0.1 to 0.6 wt % of a polyether group based on the weight of the crosslinked cellulose ether, the crosslinked cellulose ether comprising a base cellulose ether and a crosslinking bond, the crosslinking bond containing a polyether group, and the base cellulose ether is selected from the group consisting of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, methyl hydroxyethyl hydroxypropyl cellulose, ethyl hydroxyethyl cellulose, and combinations thereof.Most preferably, the free-standing film of the present invention comprises 20 to 100% by weight (preferably at least 25% by weight, more preferably at least 40% by weight, most preferably at least 60% by weight) (preferably 98% by weight or less, more preferably 95% by weight or less, most preferably 90% by weight or less) of a crosslinked cellulose ether based on the weight of the free-standing film, the crosslinked cellulose ether containing 0.1 to 0.6% by weight of a polyether group based on the weight of the crosslinked cellulose ether, the crosslinked cellulose ether comprising a base cellulose ether and a crosslinking bond, the crosslinking bond containing a polyether group, and the base cellulose ether is hydroxyethyl methylcellulose.
[0028] Preferably, the free-standing film of the present invention comprises 20 to 100% by weight (preferably at least 25% by weight, more preferably at least 40% by weight, and most preferably at least 60% by weight) (preferably 98% by weight or less, more preferably 95% by weight or less, and most preferably 90% by weight or less) of crosslinked cellulose ether based on the weight of the free-standing film, and a crosslinked cellulose ether containing 0.1 to 0.6% by weight of a polyether group based on the weight of the crosslinked cellulose ether, and all of the crosslinked celluloses are irreversibly crosslinked cellulose ethers. More preferably, the free-standing film of the present invention comprises 20 to 100% by weight (preferably at least 25% by weight, more preferably at least 40% by weight, and most preferably at least 60% by weight) (preferably 98% by weight or less, more preferably 95% by weight or less, and most preferably 90% by weight or less) of crosslinked cellulose ether based on the weight of the free-standing film, which crosslinked cellulose ether contains 0.1 to 0.6% by weight of a polyether group based on the weight of the crosslinked cellulose ether, the crosslinked cellulose ether comprises a base cellulose ether and a crosslinking bond, the crosslinking bond contains a polyether group, the base cellulose ether is a mixed cellulose ether containing a hydroxyalkyl ether group and an alkyl ether group, and all of the crosslinked celluloses are irreversibly crosslinked cellulose ethers.Even more preferably, the free-standing film of the present invention comprises 20-100 wt. % (preferably at least 25 wt. %, more preferably at least 40 wt. %, and most preferably at least 60 wt. %) (preferably 98 wt. % or less, more preferably 95 wt. % or less, and most preferably 90 wt. % or less) of a crosslinked cellulose ether based on the weight of the free-standing film, the crosslinked cellulose ether containing 0.1-0.6 wt. % of a polyether group based on the weight of the crosslinked cellulose ether, the crosslinked cellulose ether comprising a base cellulose ether and a crosslinking bond, the crosslinking bond containing a polyether group, the base cellulose ether being selected from the group consisting of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, methyl hydroxyethyl hydroxypropyl cellulose, ethyl hydroxyethyl cellulose, and combinations thereof, and any of the crosslinked celluloses being irreversibly crosslinked cellulose ethers. Most preferably, the free-standing film of the present invention comprises 20 to 100% by weight (preferably at least 25% by weight, more preferably at least 40% by weight, most preferably at least 60% by weight) (preferably 98% by weight or less, more preferably 95% by weight or less, most preferably 90% by weight or less) of a crosslinked cellulose ether based on the weight of the free-standing film, which crosslinked cellulose ether contains 0.1 to 0.6% by weight of a polyether group based on the weight of the crosslinked cellulose ether, the crosslinked cellulose ether comprises a base cellulose ether and a crosslinking bond, the crosslinking bond contains a polyether group, the base cellulose ether is hydroxyethyl methylcellulose, and each of the crosslinked celluloses is an irreversibly crosslinked cellulose ether.
[0029] Preferably, the crosslinked cellulose ether contains 0.1 to 0.6% by weight (preferably 0.12 to 0.6% by weight, more preferably 0.12 to 0.45% by weight, most preferably 0.12 to 0.29% by weight) of a polyether group based on the weight of the crosslinked cellulose ether. More preferably, the crosslinked cellulose ether contains 0.1 to 0.6% by weight (preferably 0.12 to 0.6% by weight, more preferably 0.12 to 0.45% by weight, most preferably 0.12 to 0.29% by weight) of a polyether group based on the weight of the crosslinked cellulose ether, and the polyether group is a polyoxyalkylene group having 2 to 100 (preferably 2 to 20, more preferably 3 to 15) oxyalkylene groups per crosslink. Most preferably, the crosslinked cellulose ether contains 0.1 to 0.6% by weight (preferably 0.12 to 0.6% by weight, more preferably 0.12 to 0.45% by weight, most preferably 0.12 to 0.29% by weight) of a polyether group based on the weight of the crosslinked cellulose ether, and the polyether group is a polyoxypropylene group having 2 to 100 (preferably 2 to 20, more preferably 3 to 15) oxypropylene groups per crosslink.
[0030] Preferably, the crosslinked cellulose ether comprises a base cellulose ether having a crosslinked bond containing 0.1-0.6 wt % polyether group based on the weight of the crosslinked cellulose ether. Preferably, the base cellulose ether is selected from hydroxyalkyl cellulose ethers, alkyl cellulose ethers, and combinations thereof. Examples of base cellulose ethers include, for example, methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, ethyl hydroxyethyl cellulose, methyl ethyl hydroxyethyl cellulose, hydrophobically modified ethyl hydroxyethyl cellulose, hydrophobically modified hydroxyethyl cellulose, sulfoethyl methyl hydroxyethyl cellulose, sulfoethyl methyl hydroxypropyl cellulose, and sulfoethyl hydroxyethyl cellulose. Preferably, the base cellulose ether is a mixed cellulose ether containing both hydroxyalkyl ether groups and alkyl ether groups, such as alkyl hydroxyethyl cellulose and hydroxyalkyl methyl cellulose (e.g., hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl hydroxyethyl hydroxypropyl cellulose, and ethyl hydroxyethyl cellulose).
[0031] Preferably, the base cellulose ether contains a hydroxyalkyl ether substitution. More preferably, the base cellulose ether has a degree of hydroxyethyl ether substitution MS(HE) or a degree of hydroxypropyl ether substitution MS(HP) of 1.5 to 4.5 (preferably, 2.0 to 3.0).
[0032] Preferably, the base cellulose ether contains a methyl ether substitution. More preferably, the base cellulose ether has a degree of methyl ether substitution DS(M) of 1.2 to 2.1 (preferably, 1.3 to 1.7, more preferably, 1.35 to 1.60).
[0033] Preferably, the base cellulose ether is a mixed cellulose ether containing hydroxyalkyl ether substitution and alkyl ether substitution, and more preferably, the base cellulose ether is a mixed cellulose ether having a hydroxyethyl ether substitution degree MS(HE) of 0.05 to 0.75 (preferably, 0.15 to 0.45, more preferably, 0.20 to 0.40) and a methyl ether substitution degree DS(M) of 1.2 to 2.1 (preferably, 1.3 to 1.7, more preferably, 1.35 to 1.60).
[0034] Preferably, the base cellulose ether is a mixed cellulose ether containing hydroxyalkyl ether substitution and alkyl ether substitution. More preferably, the base cellulose ether is a mixed cellulose ether having a hydroxypropyl ether substitution degree MS (HP) of 0.1 to 1.5 (preferably, 0.2 to 1.2) and a methyl ether substitution degree DS (M) of 1.2 to 2.1 (preferably, 1.3 to 2.0).
[0035] Preferably, the crosslinked cellulose ether comprises a base cellulose ether having crosslinks containing 0.1 to 0.6 weight percent polyether groups, based on the weight of the crosslinked cellulose ether, the base cellulose ether being hydroxyethyl methylcellulose and the crosslinks being polyoxypropylene dioxyethylene ether crosslinks, such as those produced as the reaction product of hydroxyethyl methylcellulose and polypropylene glycol (PPG) glycidyl ether.
[0036] The crosslinking agent used to crosslink the base cellulose ether to form a crosslinked cellulose ether includes a compound having a polyoxyalkylene or poly(alkylene) glycol group and two or more (preferably two) crosslinking groups, such as a halogen group, a glycidyl or epoxy group, and an ethylenically unsaturated group (e.g., a vinyl group) that form an ether bond with the base cellulose ether to form a crosslinked cellulose ether. Preferably, the crosslinking agent is selected from the group consisting of 1,2-dichloro(poly)alkoxyether, dichloropolyoxyethylene, diglycidyl polyalkoxyether, diglycidyl phosphonate, and divinyl polyoxyalkylene containing a sulfone group. Crosslinking agents having two different types of functional groups may be used. Examples include diglycidyl polyoxypropylene and glycidyl (poly)oxyalkyl methacrylate. Preferably, the crosslinking agent contains 2 to 100 (preferably 2 to 20, more preferably 3 to 15) oxyalkylene groups per molecule.
[0037] Preferably, the amount of crosslinking agent contained in the crosslinked cellulose ether is in the range of 0.0001 to 0.05 equivalents (preferably, 0.0005 to 0.01 equivalents, more preferably, 0.001 to 0.005 equivalents), where 1 "equivalent" represents the molar ratio of the crosslinking agent to the number of moles of anhydroglucose units (AGUs) in the base cellulose ether.
[0038] Preferably, crosslinked cellulose ether is irreversibly crosslinked cellulose ether.That is, the crosslink in crosslinked cellulose ether is not broken during intended use of crosslinked cellulose ether under normal conditions.In contrast, reversible crosslink is broken during intended use of crosslinked cellulose ether under normal conditions.An example of reversible crosslink in the cellulose ether intended for use in laundry detergent formulation is that which is produced using aldehyde crosslinking agent (e.g. glyoxal), and this crosslink is decomposed when crosslinked material is dissolved in water.
[0039] Preferably, the free-standing film of the present invention comprises (a) from 5 to 80% by weight (preferably at least 5 to 75% by weight, more preferably from 7.5 to 60% by weight, and most preferably from 10 to 40% by weight) of partially hydrolyzed poly(vinyl acetate) based on the weight of the free-standing film (preferably, the partially hydrolyzed poly(vinyl acetate) is 75 to 99% hydrolyzed (more preferably, 80 to 99% hydrolyzed, and most preferably, 90 to 99% hydrolyzed)), (b) from 0.1 to 45% by weight (preferably at least 5 to 75% by weight, more preferably, 7.5 to 60% by weight, and most preferably, 10 to 40% by weight) of the partially hydrolyzed poly(vinyl acetate) based on the weight of the free-standing film (preferably, the partially hydrolyzed poly(vinyl acetate) is 75 to 99% hydrolyzed (more preferably, 80 to 99% hydrolyzed, and most preferably, 90 to 99% hydrolyzed)), based on the weight of the free-standing film. (c) 0.1 to 45% by weight (preferably 1 to 40% by weight, more preferably 5 to 25% by weight, most preferably 10 to 15% by weight) of a crosslinking agent based on the weight of the free-standing film, and (d) 0.1 to 45% by weight (preferably 1 to 40% by weight, more preferably 5 to 25% by weight, most preferably 10 to 15% by weight) of a poly(ethylene glycol) having a weight average molecular weight of 20,000 to 2,000,000 daltons (preferably 100,000 to 1,000,000 daltons, more preferably 250,000 to 750,000 daltons, most preferably 350,000 to 650,000 daltons). (d) 0.1 to 35 wt % (preferably 1 to 25 wt %, more preferably 2 to 15 wt %, and most preferably 4 to 7.5 wt %) based on the weight of the free-standing film of a poly(alkylene glycol) having a weight average molecular weight of more than 400 to 5,300 daltons (preferably 500 to 1,500 daltons, more preferably 750 to 1,200 daltons, and most preferably 800 to 1,000 daltons); (e) 0.1 to 45 wt % (preferably 1 to 40 wt %, more preferably 2 to 35 wt %, and most preferably 4 to 7.5 wt %) based on the weight of the free-standing film of a poly(alkylene glycol) having a weight average molecular weight of more than 400 to 5,300 daltons (preferably 500 to 1,500 daltons, more preferably 750 to 1,200 daltons, and most preferably 800 to 1,000 daltons). (f) 0.1 to 10 wt. % (preferably 0.5 to 7.5 wt. %, more preferably 1 to 6 wt. %, and most preferably 2 to 5.5 wt. %) of a poly(isobutylene-co-maleic anhydride) copolymer, based on the weight of the free-standing film, which is at least partially neutralized (preferably having a degree of neutralization of 50 to 100%, more preferably 75 to 100%, and most preferably 95 to 100%), and (g) 0.01 to 1 wt. % (preferably 0.5 to 7.5 wt. %, more preferably 1 to 6 wt. %, and most preferably 2 to 5.5 wt. %) of a poly(isobutylene-co-maleic anhydride) copolymer, based on the weight of the free-standing film, which is at least partially neutralized (preferably having a degree of neutralization of 50 to 100%, more preferably 75 to 100%, and most preferably 95 to 100%), based on the weight of the free-standing film.8 wt. % poly(vinylpyrrolidone) (preferably, the poly(vinylpyrrolidone) has a weight average molecular weight of 5,000 to 2,000,000 Daltons (preferably, 10,000 to 1,500,000 Daltons, more preferably, 20,000 to 100,000 Daltons, and most preferably, 20,000 to 50,000 Daltons)) (preferably, the weight ratio of partially hydrolyzed poly(vinyl acetate) to poly(vinylpyrrolidone) in the free-standing film is greater than 10:1 (preferably, at least 100:1, more preferably, at least 150:1, and most preferably, 150:1 to 600:1)).
[0040] Preferably, the free-standing film of the present invention comprises 20-95 wt. % (preferably at least 25 wt. %, more preferably at least 40 wt. %, and most preferably at least 60 wt. %) (preferably 90 wt. % or less) of crosslinked cellulose ether, based on the weight of the free-standing film, containing 0.1-0.6 wt. % of polyether groups, based on the weight of the crosslinked cellulose ether, and 5-80 wt. % (preferably at least 5 wt. %, more preferably at least 10 wt. %) (preferably 75 wt. % or less, more preferably 60 wt. % or less, and most preferably 40 wt. % or less) of partially hydrolyzed poly(vinyl acetate) (preferably 75-99% hydrolyzed, more preferably 80-99% hydrolyzed, and most preferably 90-99% hydrolyzed), based on the weight of the free-standing film.
[0041] Preferably, the free-standing film of the present invention further comprises 5 to 80 wt% (preferably 5 to 75 wt%, more preferably 7.5 to 60 wt%, most preferably 10 to 40 wt%) (preferably at least 5 wt%, more preferably at least 10 wt%) (preferably 75 wt% or less, more preferably 60 wt% or less, most preferably 40 wt% or less) partially hydrolyzed poly(vinyl acetate) (preferably, the partially hydrolyzed poly(vinyl acetate) is 75 to 99% hydrolyzed (more preferably, 80 to 99% hydrolyzed, most preferably 90 to 99% hydrolyzed). More preferably, the free-standing film of the present invention further comprises 5 to 80 wt% (preferably, 5 to 75 wt%, more preferably 7.5 to 60 wt%, most preferably 10 to 40 wt%) based on the weight of the free-standing film. 5-60% by weight, most preferably 10-40% by weight (preferably at least 5% by weight, more preferably at least 10% by weight) (preferably 75% by weight or less, more preferably 60% by weight or less, most preferably 40% by weight or less) partially hydrolyzed poly(vinyl acetate) having a weight average molecular weight of 10,000-250,000 daltons (preferably 20,000-175,000 daltons, more preferably 30,000-100,000 daltons, most preferably 55,000-80,000 daltons) (preferably, the partially hydrolyzed poly(vinyl acetate) is 75-99% hydrolyzed (more preferably, 80-99% hydrolyzed, most preferably 90-99% hydrolyzed).
[0042] Preferably, the self-supporting film of the present invention further comprises 0.1 to 45 wt % (preferably 10 to 40 wt %, more preferably 15 to 40 wt %, most preferably 20 to 35 wt %) of a crosslinking agent based on the weight of the self-supporting film. More preferably, the self-supporting film of the present invention further comprises 0.1 to 45 wt % (preferably 10 to 40 wt %, more preferably 15 to 40 wt %, most preferably 20 to 35 wt %) of a crosslinking agent based on the weight of the self-supporting film, the crosslinking agent being an ionic crosslinking agent (e.g., an alkali metal salt, an alkali metal salt, and a mixture thereof). Preferably, the crosslinking agent is Ca 2+ , Mg 2+ , Al 2+ , Al 3+ , Zn 2+ , and mixtures thereof. More preferably, the crosslinking agent is selected from the group consisting of Ca 2+ , Zn 2+ Preferably, the cation is provided as a water soluble inorganic salt or complex, e.g., CaCl2, ZnO, zinc ammonium bicarbonate, and mixtures thereof.
[0043] Preferably, the self-supporting film of the present invention further comprises 0.1 to 45 wt% (preferably 1 to 40 wt%, more preferably 5 to 25 wt%, most preferably 10 to 15 wt%) of poly(ethylene oxide) based on the weight of the self-supporting film. More preferably, the self-supporting film of the present invention further comprises 0.1 to 45 wt% (preferably 1 to 40 wt%, more preferably 5 to 25 wt%, most preferably 10 to 15 wt%) of poly(ethylene oxide) based on the weight of the self-supporting film, the poly(ethylene oxide) having a weight average molecular weight of 20,000 to 2,000,000 daltons (preferably 100,000 to 1,000,000 daltons, more preferably 250,000 to 750,000 daltons, most preferably 350,000 to 650,000 daltons).
[0044] Preferably, the self-supporting film of the present invention further comprises 0.1 to 35 wt% (preferably 1 to 25 wt%, more preferably 2 to 15 wt%, most preferably 4 to 7.5 wt%) of poly(alkylene glycol) based on the weight of the self-supporting film. More preferably, the self-supporting film of the present invention further comprises 0.1 to 35 wt% (preferably 1 to 25 wt%, more preferably 2 to 15 wt%, most preferably 4 to 7.5 wt%) of poly(alkylene glycol) based on the weight of the self-supporting film, and the poly(alkylene glycol) has a weight average molecular weight of more than 400 to 5,300 daltons (preferably 500 to 1,500 daltons, more preferably 750 to 1,200 daltons, most preferably 800 to 1,000 daltons). Most preferably, the free-standing film of the present invention further comprises 0.1 to 35 wt % (preferably 1 to 25 wt %, more preferably 2 to 15 wt %, and most preferably 4 to 7.5 wt %) of poly(alkylene glycol) based on the weight of the free-standing film, the poly(alkylene glycol) having a weight average molecular weight of more than 400 to 5,300 daltons (preferably 500 to 1,500 daltons, more preferably 750 to 1,200 daltons, and most preferably 800 to 1,000 daltons), and the poly(alkylene glycol) is a random copolymer of ethylene oxide and propylene oxide.
[0045] Preferably, the self-supporting film of the present invention further contains 0.1 to 45 wt % (preferably 1 to 40 wt %, more preferably 2 to 35 wt %, and most preferably 5 to 25 wt %) of a plasticizer based on the weight of the self-supporting film. More preferably, the free-standing film of the present invention further comprises 0.1 to 45 wt % (preferably, 1 to 40 wt %, more preferably, 2 to 35 wt %, and most preferably, 5 to 25 wt %) of a plasticizer based on the weight of the free-standing film, the plasticizer being selected from the group consisting of dipropylene glycol, isomalt, maltitol, sorbitol, xylitol, erythritol, adonitol, dulcitol, pentaerythritol, mannitol, glycerin, diglycerin, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycols having a weight average molecular weight of up to 400 Daltons, neopentyl glycol, propylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, polyether polyols having a weight average molecular weight of up to 400 Daltons, and mixtures thereof. Even more preferably, the self-supporting film of the present invention further comprises 0.1 to 45 wt% (preferably 1 to 40 wt%, more preferably 2 to 35 wt%, most preferably 5 to 25 wt%) of a plasticizer based on the weight of the self-supporting film, the plasticizer being selected from the group consisting of dipropylene glycol, sorbitol, glycerin, and mixtures thereof. Most preferably, the self-supporting film of the present invention further comprises 0.1 to 45 wt% (preferably 1 to 40 wt%, more preferably 2 to 35 wt%, most preferably 5 to 25 wt%) of a plasticizer based on the weight of the self-supporting film, the plasticizer comprising a mixture of dipropylene glycol, sorbitol, and glycerin.
[0046] Preferably, the self-supporting film of the present invention further comprises 0.1-10 wt% (preferably 0.5-7.5 wt%, more preferably 1-6 wt%, most preferably 2-5.5 wt%) of poly(isobutylene-co-maleic anhydride) copolymer based on the weight of the self-supporting film. More preferably, the self-supporting film of the present invention further comprises 0.1-10 wt% (preferably 0.5-7.5 wt%, more preferably 1-6 wt%, most preferably 2-5.5 wt%) of poly(isobutylene-co-maleic anhydride) copolymer based on the weight of the self-supporting film, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized (preferably the degree of neutralization is 50-100%, more preferably 75-100%, most preferably 95-100%). Most preferably, the free-standing film of the present invention further comprises 0.1-10 wt. % (preferably, 0.5-7.5 wt. %, more preferably, 1-6 wt. %, and most preferably, 2-5.5 wt. %) of poly(isobutylene-co-maleic anhydride) copolymer based on the weight of the free-standing film, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized (preferably, the degree of neutralization is 50-100%, more preferably, 75-100%, and most preferably, 95-100%), and the poly(isobutylene-co-maleic anhydride) copolymer has a weight average molecular weight of 50,000-500,000 Daltons (preferably, 75,000-250,000 Daltons, more preferably, 100,000-200,000 Daltons, and most preferably, 140,000-180,000 Daltons).
[0047] Preferably, the free-standing film of the present invention further comprises 0.1-10 wt % (preferably, 0.5-7.5 wt %, more preferably, 1-6 wt %, and most preferably, 2-5.5 wt %) of poly(isobutylene-co-maleic anhydride) copolymer based on the weight of the free-standing film, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized with at least one of an alkaline earth metal hydroxide, an alkaline earth metal hydroxide, and an ionomer, and the degree of neutralization is 50-100% (more preferably, 75-100%, and most preferably, 95-100%). More preferably, the free-standing film of the present invention further comprises 0.1-10 wt. % (preferably, 0.5-7.5 wt. %, more preferably, 1-6 wt. %, and most preferably, 2-5.5 wt. %) of poly(isobutylene-co-maleic anhydride) copolymer based on the weight of the free-standing film, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized with at least one of an alkaline earth metal hydroxide and an alkaline earth metal hydroxide, and the degree of neutralization is 50-100% (more preferably, 75-100%, and most preferably, 95-100%). Most preferably, the free-standing film of the present invention further comprises 0.1-10 wt. % (preferably, 0.5-7.5 wt. %, more preferably, 1-6 wt. %, and most preferably, 2-5.5 wt. %) of poly(isobutylene-co-maleic anhydride) copolymer based on the weight of the free-standing film, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized with at least one of sodium hydroxide, potassium hydroxide, magnesium hydroxide, and calcium hydroxide, and the degree of neutralization is 50-100% (more preferably, 75-100%, and most preferably, 95-100%).
[0048] Preferably, the self-supporting film of the present invention further comprises 0.01 to 1.8 wt % of poly(vinylpyrrolidone) based on the weight of the self-supporting film. More preferably, the self-supporting film of the present invention further comprises 0.01 to 1.8 wt % of poly(vinylpyrrolidone) based on the weight of the self-supporting film, the poly(vinylpyrrolidone) having a weight average molecular weight of 5,000 to 2,000,000 daltons (preferably 10,000 to 1,500,000 daltons, more preferably 20,000 to 100,000 daltons, and most preferably 20,000 to 50,000 daltons). Most preferably, the free-standing film of the present invention further comprises 0.01 to 1.8 wt. % poly(vinylpyrrolidone), based on the weight of the free-standing film, the poly(vinylpyrrolidone) having a weight average molecular weight of 5,000 to 2,000,000 daltons (preferably, 10,000 to 1,500,000 daltons, more preferably, 20,000 to 100,000 daltons, and most preferably, 20,000 to 50,000 daltons), and the weight ratio of partially hydrolyzed poly(vinyl acetate) to poly(vinylpyrrolidone) in the free-standing film is greater than 10:1 (preferably, at least 100:1, more preferably, at least 150:1, and most preferably, 150:1 to 600:1).
[0049] Preferably, the free-standing film of the present invention further comprises 0-10 wt.% of optional additives. More preferably, the free-standing film of the present invention further comprises 0-10 wt.% of optional additives, the optional additives being selected from the group consisting of preservatives, antioxidants, viscosity modifiers, solubility modifiers, antimicrobial agents, binding agents, chelating agents, fillers, extenders, antifoaming agents, lubricants, release agents, antiblocking agents, tackifiers, coalescing agents, detackifiers, and nanoparticles (e.g., silicate-type nanoclays).
[0050] Preferably, the free-standing film of the present invention further comprises 0-10 wt% of an optional additive, the optional additive comprising nanoparticles (preferably silicate nanoclay). More preferably, the free-standing film of the present invention further comprises 0.05-1 wt% (more preferably 0.1-0.5 wt%, most preferably 0.1-0.3 wt%) of nanoparticles (preferably silicate nanoclay). Most preferably, the free-standing film of the present invention comprises 0.1-0.3 wt% of nanoparticles (preferably silicate nanoclay).
[0051] Preferably, the free-standing film of the present invention further comprises 0-10 wt% of optional additives, the optional additives further comprising an antifoaming agent. More preferably, the free-standing film of the present invention further comprises 1-10 wt% (more preferably, 2-7.5 wt%, most preferably, 3-6 wt%) of an antifoaming agent. Most preferably, the free-standing film of the present invention comprises 3-6 wt% of an antifoaming agent.
[0052] The water-soluble films of the present invention can be prepared by techniques known to those skilled in the art, including by solution casting onto a substrate such as glass, polyethylene terephthalate (PET), or metal. Typically, water is used as the solvent for solution casting, although other solvents may be used. After casting, the film may be dried by heating at an elevated temperature, e.g., 65-80°C.
[0053] The self-supporting film of the present invention has utility as a water-soluble (preferably cold water-soluble) packaging film that facilitates the dosing of materials, for example household care compositions such as pre-measured unit doses of hard surface cleaning formulations, dish care formulations, automatic dishwashing rinse aid formulations, laundry detergent formulations, or fabric conditioner formulations.Preferably, the self-supporting film of the present invention forms a cavity.More preferably, the self-supporting film of the present invention forms a cavity, which is enclosed by the self-supporting film.
[0054] Preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a detergent formulation. More preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a detergent formulation, the self-supporting film forming a cavity, the detergent formulation disposed within the cavity, and the detergent formulation in contact with the self-supporting film. Even more preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a detergent formulation, the self-supporting film forming a cavity, the detergent formulation disposed within the cavity, the self-supporting film encapsulating the cavity, and the detergent formulation in contact with the self-supporting film. Most preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a detergent formulation comprising 10-60% by weight of a surfactant based on the weight of the detergent formulation (preferably, the surfactant is selected from the group consisting of cationic surfactants, anionic surfactants, nonionic surfactants, zwitterionic surfactants, and mixtures thereof, more preferably, the surfactant comprises a nonionic surfactant), wherein the self-supporting film forms a cavity, the detergent formulation is disposed within the cavity, the self-supporting film encapsulates the cavity, and the detergent formulation is in contact with the self-supporting film.
[0055] Preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a detergent formulation, the self-supporting film forming a sealed container to house the detergent formulation. The sealed container can be formed by any suitable method, including processes and features such as heat sealing, solvent welding, and adhesive sealing solutions (e.g., using water-soluble adhesives).
[0056] Preferably, the detergent formulations used in the unit dose detergent packages of the present invention further comprise optional ingredients selected from the group consisting of preservatives, antioxidants, viscosity modifiers, solubility modifiers, antimicrobial agents, binding agents, chelating agents, germicides, aesthetic enhancers, and fillers.
[0057] Preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a detergent formulation, the detergent formulation being a hard surface cleaning concentrate. More preferably, the unit dose detergent package of the present invention comprises a self-supporting film of the present invention and a hard surface cleaning concentrate, the hard surface cleaning concentrate comprising a glycol ether of formula I (preferably 15 to 50 wt. % (more preferably 20 to 40 wt. %, even more preferably 25 to 30 wt. %, and most preferably 26 to 28 wt. %) of the glycol ether of formula I, based on the weight of the hard surface cleaning concentrate). R 1 -O-[CHCH(R 2 )O] a -H(I) [In the formula, R 1 is linear or branched C 2~8 is an alkyl group, and each R 2 are independently selected from the group consisting of hydrogen and methyl groups, and a is 1 to 3; and a nonionic surfactant of formula II (preferably, 10 to 60 wt. % (more preferably, 25 to 50 wt. %, even more preferably, 30 to 40 wt. %, and most preferably, 34 to 38 wt. %) of the nonionic surfactant of formula II, based on the weight of the hard surface cleaning concentrate).
[0058] [ka] [In the formula, w is an average of 5 to 40 (preferably 7 to 27, more preferably 8 to 20, and most preferably 7 to 12), and R 3 is hydrogen and linear or branched C 1~20 alkyl groups; R 4 is linear or branched C 1~20 is an alkyl group, and each R 5 is selected from the group consisting of hydrogen, methyl, ethyl, n-propyl, iso-propyl, n-butyl, 2-butyl, and 2-methyl-2-butyl (preferably, hydrogen, methyl, and ethyl, more preferably, hydrogen and methyl, and most preferably, hydrogen), with the proviso that R 3 and R 4the sum of the total number of carbon atoms is 5 to 21], and a tertiary amine (preferably 15 to 60 wt. % (more preferably 20 to 50 wt. %, even more preferably 25 to 40 wt. %, and most preferably 27 to 34 wt. %) of the tertiary amine, based on the weight of the hard surface cleaning concentrate) (preferably the tertiary amine is of formula III).
[0059] [ka] [In the formula, R 6 , R 7 , and R 8 is linear or branched C 1~20 Alkyl groups and linear or branched C 1~20 Hydroxyalkyl groups (preferably linear or branched C 1~10 Alkyl groups and linear or branched C 1~10 Hydroxyalkyl groups, more preferably branched C 3~5 Alkyl group or branched C 3~5 hydroxyalkyl groups, most preferably branched C3 hydroxyalkyl groups), and a water-soluble film encapsulating the concentrated hard surface cleaning composition.
[0060] Preferably, the unit dose detergent package of the present invention is a hard surface cleaning concentrate comprising from 15 to 50% (preferably from 20 to 40%, more preferably from 25 to 30%, and most preferably from 26 to 28%) by weight of a glycol ether of formula I, based on the weight of the hard surface cleaning concentrate. R 1 -O-[CHCH(R 2 )O] a -H(I) [In the formula, R 1 is linear or branched C 2~8 Alkyl groups (preferably linear or branched C 3~8 Alkyl groups, more preferably linear C 4~7 alkyl group, most preferably a linear C alkyl group), and each R 2 are independently selected from the group consisting of hydrogen and a methyl group (preferably, each R2 R is hydrogen, and a is 1 to 3 (preferably a is 2). More preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 15 to 50% (preferably 20 to 40%, more preferably 25 to 30%, and most preferably 26 to 28%) by weight of the hard surface cleaning concentrate of a glycol ether of formula I, 1 is linear C 4~7 Most preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 15 to 50% (preferably 20 to 40%, more preferably 25 to 30%, and most preferably 26 to 28%) by weight of the hard surface cleaning concentrate of a glycol ether of formula I, where R 1 is a linear C6 alkyl group and a is 2.
[0061] Preferably, the unit dose detergent package of the present invention is a hard surface cleaning concentrate comprising from 15 to 50% (preferably from 20 to 40%, more preferably from 25 to 30%, and most preferably from 26 to 28%) by weight of the hard surface cleaning concentrate of a glycol ether of formula I (the glycol ether of formula I is of formula Ia):
[0062] [ka] [In the formula, R 1 is linear or branched C 2~8 Alkyl groups (preferably linear or branched C 3~8 Alkyl groups, more preferably linear C 4~7More preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising from 15 to 50% (preferably from 20 to 40%, more preferably from 25 to 30%, most preferably from 26 to 28%) by weight of a glycol ether of formula Ia, where R 1 is a linear C 4~7 Most preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 15 to 50% (preferably 20 to 40%, more preferably 25 to 30%, most preferably 26 to 28%) by weight of the hard surface cleaning concentrate of a glycol ether of formula Ia, where R 1 is a linear C6 alkyl group, b is 2, and c is 0.
[0063] Preferably, the unit dose detergent package of the present invention is a hard surface cleaning concentrate comprising from 10 to 60% (preferably, from 25 to 50%, more preferably, from 30 to 40%, most preferably, from 34 to 38% (35%, 36%) by weight of a nonionic surfactant of formula II based on the weight of the hard surface cleaning concentrate.
[0064] [ka] [In the formula, w is an average of 5 to 40 (preferably 7 to 27, more preferably 8 to 20, and most preferably 7 to 12), and R 3 is hydrogen and linear or branched C 1~20 Alkyl groups (preferably hydrogen and linear or branched C 1~15 Alkyl groups, more preferably hydrogen and linear C 1~15alkyl groups), R 4 is linear or branched C 1~20 Alkyl groups (preferably linear or branched C 1~15 Alkyl groups, more preferably linear C 1~15 alkyl group), and each R 5 are independently selected from the group consisting of hydrogen, methyl, ethyl, n-propyl, iso-propyl, n-butyl, 2-butyl, and 2-methyl-2-butyl (preferably hydrogen, methyl, and ethyl, more preferably hydrogen and methyl, and most preferably hydrogen), with the proviso that R 3 and R 4 wherein the sum of the total number of carbon atoms in is 5 to 21 (preferably 6 to 20 carbon atoms, more preferably 7 to 18 carbon atoms, and most preferably 11 to 15 carbon atoms). More preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 20 to 60% (preferably 25 to 50% by weight, more preferably 30 to 40% by weight, and most preferably 34 to 38% by weight) (35% by weight, 36% by weight) of a nonionic surfactant of formula II, 3 is hydrogen and linear C 1~15 alkyl groups; R 4 is linear or branched C 1~15 is an alkyl group, where R 3 and R 4 wherein the sum of the total number of carbon atoms in R is 6 to 20. Most preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 20 to 60% (preferably 25 to 50%, more preferably 30 to 40%, most preferably 34 to 38%) (35%, 36%) by weight of the hard surface cleaning concentrate of a nonionic surfactant of formula II, 3 is hydrogen and linear C 1~15 alkyl groups; R 4 is a linear C 1~15 is an alkyl group, where R3 and R 4 The total number of carbon atoms in the formula (I) is 7 to 18.
[0065] Preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 20-60% (preferably 25-50%, more preferably 30-40%, and most preferably 34-38%) by weight of the hard surface cleaning concentrate of a nonionic surfactant of formula II, the nonionic surfactant being of formula IIa.
[0066] [ka] [In the formula, x is an average of 5 to 15 (preferably 7 to 12, more preferably 8 to 10), y is an average of 0 to 15 (preferably 0 to 10, more preferably 0 to 8, most preferably 0 to 6), and R 3 is hydrogen and linear or branched C 1~20 Alkyl groups (preferably hydrogen and linear or branched C 1~15 Alkyl groups, more preferably hydrogen and linear C 1~15 alkyl groups), R 4 is linear or branched C 1~20 Alkyl groups (preferably linear or branched C 1~15 Alkyl groups, more preferably linear C 1~15 alkyl groups), where R 3 and R 4 and the sum of the total number of carbon atoms in each of the groups is 5 to 21 (preferably 6 to 20 carbon atoms, more preferably 7 to 18 carbon atoms, and most preferably 11 to 15 carbon atoms). More preferably, the unit dose detergent package of the present invention is a hard surface cleaning concentrate comprising 20 to 60% (preferably 25 to 50% by weight, more preferably 30 to 40% by weight, and most preferably 34 to 38% by weight) of a nonionic surfactant of formula IIa,3 is hydrogen and linear C 1~15 alkyl groups; R 4 is linear or branched C 1~15 is an alkyl group, where R 3 and R 4 wherein the sum of the total number of carbon atoms in is 6 to 20. Most preferably, the unit dose package of the present invention comprises a hard surface cleaning concentrate comprising 20 to 60% (preferably 25 to 50%, more preferably 30 to 40%, and most preferably 34 to 38%) by weight of the hard surface cleaning concentrate of a nonionic surfactant of formula IIa, 3 is hydrogen or linear C 1~15 alkyl groups; R 4 is a linear C 1~15 is an alkyl group, where R 3 and R 4 The total number of carbon atoms in the formula (I) is 7 to 18.
[0067] Preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 15-60% (preferably 20-50%, more preferably 25-40%, most preferably 27-34%) by weight of a tertiary amine based on the weight of the hard surface cleaning concentrate. More preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising 15-60% (preferably 20-50%, more preferably 25-40%, most preferably 27-34%) by weight of a tertiary amine based on the weight of the hard surface cleaning concentrate, wherein the tertiary amine is according to formula III.
[0068] [ka] [In the formula, R 6 , R 7 , and R 8 is linear or branched C 1~20Alkyl groups (preferably linear or branched C 1~10 Alkyl groups and linear or branched C 1~10 Hydroxyalkyl groups, more preferably branched C 3~5 Alkyl group or branched C 3~5 Even more preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising from 15 to 60% (preferably, 20 to 50%, more preferably, 25 to 40%, and most preferably, 27 to 34%) by weight of a tertiary amine of formula III, where R 6 , R 7 , and R 8 is linear or branched C 1~10 Alkyl groups and linear or branched C 1~10 Even more preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising from 15 to 60% (preferably, from 20 to 50%, more preferably, from 25 to 40%, and most preferably, from 27 to 34%) by weight of the hard surface cleaning concentrate of a tertiary amine of formula III, wherein R 6 , R 7 and R 8 is a branched C 3~5 Alkyl groups and branched C 3~5 Most preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate comprising from 15 to 60% (preferably, from 20 to 50%, more preferably, from 25 to 40%, and most preferably, from 27 to 34%) by weight of the hard surface cleaning concentrate of a tertiary amine of formula III, wherein R 6 , R 7 and R 8 is a branched C3 hydroxyalkyl group.
[0069] Preferably, the unit dose detergent package of the present invention comprises a hard surface cleaning concentrate, which optionally further comprises optional ingredients. Preferably, the hard surface cleaning concentrate further comprises optional ingredients, which are selected from the group consisting of salts, enzymes, corrosion inhibitors, acids, bleaches, abrasives, antimicrobial agents (e.g., phenoxyethanol, benzalkonium chloride), rheology modifiers, film formers (e.g., Acusol™ Pro), pH adjusters, buffers, aesthetic colors, fragrances, and mixtures thereof.
[0070] Preferably, the hard surface cleaning concentrate has a pH of less than or equal to 11. More preferably, the hard surface cleaning concentrate has a pH of from 5 to 10.5. Most preferably, the hard surface cleaning concentrate has a pH of from 8 to 10.
[0071] Preferably, the hard surface cleaning concentrate comprises 0 to 10 wt. % water (preferably, 0 to 5 wt. %, more preferably, 0 to 2.5 wt. %, even more preferably, 0 to 2 wt. %, still more preferably, 0 to 1.5 wt. %, and most preferably, 0 to 1 wt. %) based on the weight of the hard surface cleaning concentrate.
[0072] Preferably, the hard surface cleaning concentrate of the present invention comprises less than 0.01 wt. % (preferably less than 0.001 wt. %, more preferably less than 0.0001 wt. %, even more preferably less than 0.0001 wt. %, most preferably below the detection limit) of a dispersant polymer based on the weight of the hard surface cleaning concentrate. More preferably, the hard surface cleaning concentrate comprises less than 0.01 wt. % (preferably less than 0.001 wt. %, more preferably less than 0.0001 wt. %, even more preferably less than 0.0001 wt. %, most preferably below the detection limit) of a dispersant polymer based on the weight of the hard surface cleaning concentrate, the dispersant polymer being selected from the group consisting of poly(acrylic acid), poly(acrylic acid / maleic acid) copolymers, poly(maleic acid / olefin) copolymers, phosphinocarboxylated polymers and mixtures thereof.
[0073] Preferably, the hard surface cleaning concentrate contains less than 0.01% (preferably less than 0.001%, more preferably less than 0.0001%, even more preferably less than 0.0001%, and most preferably below the limit of detection) quaternary ammonium compounds by weight based on the weight of the hard surface cleaning concentrate.
[0074] Preferably, the hard surface cleaning concentrate comprises less than 0.01 wt. % (preferably less than 0.001 wt. %, more preferably less than 0.0001 wt. %, even more preferably less than 0.0001 wt. %, most preferably below the detection limit) of a hydrotrope based on the weight of the hard surface cleaning concentrate. More preferably, the hard surface cleaning concentrate comprises less than 0.01 wt. % (preferably less than 0.001 wt. %, more preferably less than 0.0001 wt. %, even more preferably less than 0.0001 wt. %, most preferably below the detection limit) of a hydrotrope based on the weight of the hard surface cleaning concentrate, the hydrotrope being selected from the group consisting of calcium, sodium, potassium, ammonium and alkanolammonium salts of xylene sulfonic acid; calcium, sodium, potassium, ammonium and alkanolammonium salts of toluene sulfonic acid; calcium, sodium, potassium, ammonium and alkanolammonium salts of ethylbenzene sulfonic acid; calcium, sodium, potassium, ammonium and alkanolammonium salts of cumene sulfonic acid; and mixtures thereof.
[0075] Some embodiments of the present invention will now be described in detail in the following examples.
[0076] Synthesis S1: Crosslinked cellulose ether The crosslinker used in synthesis S1 was a linear poly(propylene glycol) diglycidyl ether made from polypropylene glycol (PPG) having a molecular weight of approximately 400 daltons and the formula:
[0077] [ka] [wherein n is 5.7 to 6.7 (EPILOX™ M985 poly(propylene glycol) diglycidyl ether crosslinker available from Leuna-Harze GmbH, Leuna, DE)].
[0078] Milled cellulose floc (1.5 mol) was added to a 5 L autoclave. The autoclave was purged with nitrogen gas three times and the contents of the autoclave were then heated to 40° C. Dimethyl ether (DME, 4.7 mol / mol anhydroglucose units (AGU)) and methyl chloride (MCl, 3.2 mol / mol AGU) were then injected into the autoclave. Caustic soda (NaOH, 50 wt% strength aqueous, 1.9 mol NaOH / mol AGU) was added to the autoclave in three portions over a period of 2 minutes at a temperature of 40° C. The reaction mixture was held at 40° C. for 30 minutes. Ethylene oxide (0.45 mol / mol AGU) was then added and the reaction mixture was held at 40° C. for 10 minutes. The crosslinker (EPILOX™ M985 crosslinker, 0.0025 mol / mol AGU) was dissolved in 20 mL of isopropanol and added to the contents of the autoclave in six portions spaced 30 seconds apart. The contents of the autoclave were then heated to 80° C. in 40 minutes. At 80° C., a water-soluble monovalent copper ligand (MCL 2, 1.3 mol / mol AGU) was rapidly injected into the autoclave. NaOH (0.67 mol / mol AGU) was then added in seven portions over 30 minutes, followed by a cook-off period of 70 minutes at 80° C. Following this, the product crosslinked cellulose ether was washed in hot water (>95° C.), neutralized with formic acid, granulated, dried, and milled.
[0079] Comparative Examples C1-C18 and Examples 1-15: Film / Additive Blends Water-soluble film / additive blends were prepared according to Comparative Examples C1-C18 and Examples 1-15 by mixing together the components in the concentrations listed in Table 1.
[0080] [Table 1]
[0081] Viscosity measurements of films blended with additives The viscosities of the water-soluble film / additive blends prepared according to Comparative Examples C1-C18 and Examples 1-15 were measured using a Brookfield DV-II programmable viscometer equipped with a CP-52 spindle at 25° C. Measurements were made for each blend at 5 rpm, 10 rpm, 20 rpm, and 50 rpm and are reported in Table 2.
[0082] [Table 2]
[0083] Examples 16 to 25: Water-soluble films Water-soluble films were formed in each of Examples 16-25 by placing a water-soluble film / additive blend prepared according to one of Examples 1-10, as described in Table 3, in a ventilated oven at 60° C. and drying to form a film. Once formed, the film was then redispersed in water to form a 1 wt. % aqueous solution in water. The viscosity of these 1 wt. % solutions was then measured at 25° C. using a Brookfield DV-II programmable viscometer equipped with a CP-52 spindle. Measurements were made for each blend at 5 rpm, 10 rpm, 20 rpm, and 50 rpm and are reported in Table 3.
[0084] [Table 3]
[0085] Synthesis S2: Concentrated hard surface cleaning composition A synthetic S2 concentrated hard surface cleaning composition was prepared by mixing the ingredients together in the weight ratios set forth in Table 4.
[0086] [Table 4]
[0087] Resistance of the film to concentrated hard surface cleaning compositions A droplet of a concentrated hard surface cleaning composition prepared according to Synthesis S2 was applied to the surface of a water-soluble film formed according to each of Examples 16 to 25. Each film was observed to resist penetration of the concentrated hard surface cleaning composition for over a period of one month.
[0088] Composite S3: Freestanding film The crosslinked cellulose ether (1 g) prepared according to Synthesis S1, calcium chloride dihydrate (0.4 g), and deionized water (98.6 g) were mixed together, and the mixture was then deposited on a substrate and dried in a ventilated oven at 60° C. to form a film.
[0089] Resistance of free-standing films to concentrated hard surface cleaning compositions A concentrated hard surface cleaning composition (1 mL) prepared according to Synthesis S2 was added to an Eppendorf tube. A free-standing film prepared according to Synthesis S3 was used to cap the opening of the Eppendorf tube. The Eppendorf tube was then inverted so that the opening was facing down, such that the concentrated hard surface cleaning composition in the tube was supported by the free-standing film. The free-standing film was observed to resist the concentrated hard surface cleaning composition for one month without penetration.
Claims
1. A free-standing film, 1. A free-standing film comprising 20 to 100 weight percent of an irreversibly crosslinked cellulose ether, based on the weight of the free-standing film, the irreversibly crosslinked cellulose ether containing 0.1 to 0.6 weight percent of a polyether group, based on the weight of the crosslinked cellulose ether.
2. 10. The free-standing film of claim 1 having an average thickness of 5 to 200 μm.
3. 3. The free-standing film of claim 2, wherein the polyether groups in the irreversibly crosslinked cellulose ether are polyoxyalkylene groups having from 2 to 100 oxyalkylene groups.
4. 4. The free-standing film of claim 3, wherein the polyoxyalkylene group is selected from the group consisting of polyoxyethylene, polyoxypropylene, and combinations thereof.
5. 5. The free-standing film of claim 4, wherein the irreversibly crosslinked cellulose ether comprises a base cellulose ether and a crosslink, the crosslink containing the polyether group, and the base cellulose ether containing a hydroxyalkyl ether group and an alkyl ether group.
6. 6. The free-standing film of claim 5, wherein the base cellulose ether is selected from the group consisting of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, methylhydroxyethyl hydroxypropyl cellulose, ethylhydroxyethyl cellulose, and combinations thereof.
7. (a) 5 to 80 weight percent, based on the weight of the free-standing film, of partially hydrolyzed poly(vinyl acetate); (b) 0.1 to 45 weight percent of a crosslinking agent, based on the weight of the free-standing film; (c) 0.1 to 45 weight percent, based on the weight of the free-standing film, of poly(ethylene oxide) having a weight average molecular weight of 20,000 to 2,000,000 daltons; (d) 0.1 to 35 weight percent, based on the weight of the free-standing film, of a poly(alkylene glycol) having a weight average molecular weight of greater than 400 to 5,300 daltons; (e) 0.1 to 45 weight percent of a plasticizer, based on the weight of the free-standing film; (f) 0.1 to 10 weight percent, based on the weight of the free-standing film, of a poly(isobutylene-co-maleic anhydride) copolymer, the poly(isobutylene-co-maleic anhydride) copolymer being at least partially neutralized; and (g) 0.01 to 1.8 weight percent poly(vinylpyrrolidone), based on the weight of the free-standing film. The free-standing film of claim 6 further comprising at least one of:
8. 20 to 95 weight percent of the crosslinked cellulose ether, based on the weight of the free-standing film, the crosslinked cellulose ether containing 0.1 to 0.6 weight percent of polyether groups, based on the weight of the crosslinked cellulose ether; 5 to 80 weight percent of the partially hydrolyzed poly(vinyl acetate), based on the weight of the free-standing film; The free-standing film of claim 7 , comprising:
9. 10. The freestanding film of claim 8, further comprising optional additives selected from the group consisting of preservatives, antioxidants, viscosity modifiers, solubility modifiers, antimicrobial agents, binders, chelating agents, fillers, extenders, antifoaming agents, lubricants, release agents, antiblocking agents, tackifiers, coalescing agents, detackifying agents, and nanoparticles.
10. 1. A unit dose detergent package comprising: A free-standing film according to claim 1; A detergent formulation comprising 10-60% by weight of a surfactant based on the weight of the detergent formulation; Including, A unit dose detergent package, wherein the self-supporting film defines a cavity, the detergent formulation is disposed within the cavity, the detergent formulation is in contact with the self-supporting film, and the self-supporting film encapsulates the detergent formulation.